The impact of body mass index on growth, schooling, productivity, and savings: A cross-country study - Aysit Tansel; Ceyhan Öztürk; Erkan Erdil (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
We examine the relationship between wealth and health through prominent growth indicators and cognitive ability. Cognitive ability is represented by nutritional status. In this study, the proxy variable for nutritional status is BMI since there is a strong relationship between cognitive ability and nutrition. We use the reduced form equation in the cubic specification of time preference rate to estimate this relationship. We assume that the time preference rate is one of the outputs of cognitive ability. The growth indicators utilized are GDP per capita, schooling, overall and manufacturing productivities, and savings. We estimate our models using the FE, GMM estimators, and long difference OLS and IV estimation through balanced panel data for 47 countries for the 1980-2009 period, which is a representative period of the neo-liberal and globalization economic policy implications. Furthermore, by using the 1980-2009 period, we may eliminate the ripple effects of the 2007-2009 financial crisis. Although there is ample evidence that the association between GDP per capita, overall and manufacturing productivities, and BMI could be cubic, we take the results of the long-difference quadratic specification into consideration and conclude that the relationship between all prominent growth indicators and BMI is inverse U-shaped. In other words, cognitive ability has a significant potential to progress growth and economic development only in a healthy status.
Keywords: E21; I15; I25; J24; O11; Q18; 330; Cognitive ability; time preference rate; BMI; productivity; health; schooling; growth; economic development